2022
DOI: 10.15620/cdc:120292
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Mortality by Usual Occupation and Industry: 46 States and New York City, United States, 2020

Abstract: This report describes COVID-19 mortality in 2020 among U.S. residents in 46 states and New York City by usual occupation and industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
(30 reference statements)
5
24
2
Order By: Relevance
“…Regardless of the claim filing rates, award proportions were low: only 441 of the 3441 claims (11.4%) from transportation and logistics were awarded compensation of any kind. Our analysis notably did not replicate the findings in some other states that workers in the manufacturing, construction, and agriculture suffered COVID-19–associated outbreaks and deaths 3,5–9,51–53 …”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Regardless of the claim filing rates, award proportions were low: only 441 of the 3441 claims (11.4%) from transportation and logistics were awarded compensation of any kind. Our analysis notably did not replicate the findings in some other states that workers in the manufacturing, construction, and agriculture suffered COVID-19–associated outbreaks and deaths 3,5–9,51–53 …”
Section: Discussioncontrasting
confidence: 96%
“…This finding is consistent with existing evidence demonstrating an increased risk of COVID-19 infection, mortality, and claim filing rates among transportation workers. 50 53 However, the rate may be an overestimate; the number of local messengers and delivery workers working in NYS in 2020 and 2021 may have been higher than what was estimated by the BLS. Regardless of the claim filing rates, award proportions were low: only 441 of the 3441 claims (11.4%) from transportation and logistics were awarded compensation of any kind.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study that measured COVID-19 mortality rates by industry and occupation, many of the same essential industries found to have elevated mortality rates for COVID-19 in that study also have low rates of access to paid sick leave in this study. 27 Many of the occupation groups identified as having a low availability of paid sick leave in this study also were found to have high mortality rates from COVID-19 in a study conducted using data from Massachusetts. 25 In addition, many of the industry and occupation groups identified as having a low availability of paid sick leave in this study also had high rates of COVID-19 infections in a study conducted in Wisconsin.…”
Section: Discussionmentioning
confidence: 58%
“…These disparities in the access and use of paid sick leave may contribute to similar disparities in the risk for COVID-19 according to geography, 20 race/ethnicity, 21 , 22 and educational attainment. 23 , 24 There are also disparities in the risk of COVID-19 outcomes according to other factors that may be associated with access to paid sick leave access including occupation, 25 , 26 industry, 27 income, 28 and insurance status. 29 , 30 Research has suggested that the expansion of access to paid sick leave that came with the Families First Coronavirus Response Act may have resulted in reductions in the number of workers getting COVID-19.…”
mentioning
confidence: 99%